Development of micro end milling process for fabricating MEMS - Ali, Mohammad Yeakub (International Islamic University Malaysia, 2009)
The influences of selected micro end milling cutting parameters on surface roughness were studied on beryllium copper alloy and PMMA (poly-methyl-methacrylate). A number of microchannels were fabricated in order to characterize the process parameters influencing surface roughness. Two-level four-factor statistical models were developed to predict the average (Ra) and peak-to-valley (Rt) surface roughness for beryllium copper alloy. Relationship of cutting speed and feed rate on surface roughness of PMMA were plotted and analyzed. Experiments were conducted with four process parameters: feed rate, depth of cut, cutting speed and tool diameter. The interaction effect of parameters was studied. Both Ra and Rt were found strongly influenced by feed per tooth, depth of cut and tool diameter. An average surface roughness of 0.30 μm for beryllium copper and 3.46 μm was observed. Furthermore, the burr height formed during machining is in the range of 15-55 μm. Burr height formation of machined microchannel was increasing proportionally with respect to cutting speeds and feed per tooth. Therefore, of low cutting speed and feed per tooth is used in microchannel fabrication to minimize the burr height.